2020
DOI: 10.3390/ma13122756
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High Temperature Synthesis on the Structure of Graphitic Carbon Nitride and Its Hydrogen Generation Ability

Abstract: Graphitic carbon nitride (g-C3N4) was obtained by thermal polymerization of dicyandiamide, thiourea or melamine at high temperatures (550 and 600 °C), using different heating rates (2 or 10 °C min−1) and synthesis times (0 or 4 h). The effects of the synthesis conditions and type of the precursor on the efficiency of g-C3N4 were studied. The most efficient was the synthesis from dicyandiamide, 53%, while the efficiency in the process of synthesis from melamine and thiourea were much smaller, 26% and 11%, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 71 publications
7
31
0
Order By: Relevance
“…Therefore, as a better option, it can be utilized as a sacrificial agent in the photocatalytic decomposition of water [25]. Our earlier results [19] suggested that g-C 3 N 4 can be an interesting alternative to the commonly used photocatalysts in water/methanol decomposition.…”
Section: Photocatalytic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, as a better option, it can be utilized as a sacrificial agent in the photocatalytic decomposition of water [25]. Our earlier results [19] suggested that g-C 3 N 4 can be an interesting alternative to the commonly used photocatalysts in water/methanol decomposition.…”
Section: Photocatalytic Activitymentioning
confidence: 99%
“…In addition, the production by condensation of simple nitrogen-rich compounds such as urea [13,14], thiourea [15], melamine [16,17], and dicyandiamide (DCDA) [18] is easy and cheap. Its additional advantage is that, depending on the type of precursor and condensation conditions, final carbon nitride can have different physicochemical properties [19]. Since the first reports on the photocatalytic properties of g-C 3 N 4 [20], attempts have been made to enhance its effectiveness, mainly by the addition of heteroatoms [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…However, some authors have reported that the presence of nitrogen does favor CO 2 capture [ 6 , 7 ], but their synthetic method is completely different. Some authors have developed other types of strategies to generate carbons doped with nitrogen, basically using a ball mill, where they jointly grind a carbon precursor such as graphene oxide and melamine, also synthesize C 3 N 4 in a similar way, where they show that the new generated material ostensibly improves the catalytic properties in the ORR [ 8 , 9 , 10 ]. We can conclude that the presence of N is necessary, but only once what type of N is adequate for the capture to be more efficient has been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Metal acetylacetonates are compounds derived from the acetylacetonate anion and metal ions [ 1 ] and they are currently utilized in a plethora of applications, such as precursors for catalysis [ 2 ], for the development of hybrid nanomaterials or membranes with enhanced gas separation performance [ 3 ], in energy storage applications [ 4 , 5 ], in sensor designs [ 6 , 7 ], in oxygen reduction reaction [ 8 , 9 ] or in generation of hydrogen [ 10 ].…”
Section: Introductionmentioning
confidence: 99%